Paragonimiasis (invasion by pulmonary flukes) - S. B. Chuelov; A. L. Rossina (LLC "Diagnostics and Vaccines", 2021)
The paper summarizes the information currently available in the literature on the etiology, life cycle, epidemiology, pathogenesis, pathomorphology, clinical manifestations, diagnosis, etiotropic therapy and prevention of paragonimiasis.